Direct demonstration of photoluminescence originated from surface functional groups in carbon nanodots. (November 2016) - Nguyen, Vanthan; Si, Jinhai; Yan, Lihe; Hou, Xun
Abstract: Carbon nanodots (C-dots) are promising substitutes for the present fluorescent nanomaterials of various applications due to their unique combination properties of intense photoluminescence (PL), low toxicity, and high aqueous solubility. However, the origin of the fascinating PL in C-dots is still a matter of current debate. Due to their complex and uncontrollable structures, the contributions of surface chemicals and carbogenic-core to their PL are poorly understood. Here, a facile two-step method combining laser ablation and UV light irradiation has been developed, in which non-fluorescent C-dots are prepared by ablating graphite powders in water using nanosecond laser, and the PL intensities are enhanced by UV light irradiation in oxygen atmosphere. Using this strategy, we are able to control the size and the surface functional groups of C-dots independently. By detailed characterization and comparison of different C-dots, we find that the intense PL in C-dots is originated from abundant surface functional groups on its surface rather than its carbogenic-core. One kind of surface functional group forms a single surface state energy level and becomes an isolated emission center with specific carrier dynamics on the surface site of C-dots. The energy gap of each surface state exhibits carbogenic-core size independent and is characterized by distinct central energies, such as CO group at 335 nm, and CO group at 430 nm.